Characterisation of an urban bridge portfolio and multi-risk prioritisation accounting for deterioration and seismic vulnerability. (March 2023) - Saler, Elisa; Donà, Marco; Pernechele, Valentina; Tecchio, Giovanni; da Porto, Francesca
Abstract: This contribution proposes a procedure to prioritise retrofit interventions on stocks of bridges according to their seismic vulnerability. The procedure also combines a previously presented approach to evaluate deterioration effects on bridges at a territorial scale. Thereby, the combination of the two approaches provides a multi-risk classification method for bridge stocks. This method also allows refined prioritisation within each class, based on the proposed quantitative indices and on multicriteria decision-making methods. The method was applied to the bridge stock managed by the municipality of Padova, in North-East Italy. First, an extensive characterisation of the analysed stock is provided, according to typological, geometric, and structural parameters. Then, the application of the combined approach is presented, highlighting which bridge types resulted more vulnerable to either seismic actions or deterioration effects.